2017
DOI: 10.1002/hep4.1061
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA AK054921 and AK128652 are potential serum biomarkers and predictors of patient survival with alcoholic cirrhosis

Abstract: Background Alcoholic liver disease (ALD) is one of the leading causes of chronic liver disease. Recent studies have demonstrated the roles of long noncoding RNAs (lncRNAs) in the pathogenesis of several disease processes. However, the roles of lncRNAs in patients with ALD remain unexplored. Methods Global profiling for human lncRNAs from peripheral blood RNA was performed in a well characterized cohort of healthy controls (HC, n=4), excessive drinkers without liver diseases (ED, n=4), and those with alcoholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…Recent studies also suggest the involvement of long noncoding RNAs (lncRNAs) in the pathogenesis of ALD. Yang et al 71 showed that lncRNAs, AK054921 and AK128652, are the two most abundantly expressed lncRNAs in normal human liver and that their levels were significantly elevated during ALD progression, indicating these two lncRNAs as novel candidates for ALD biomarkers. Whether these lncRNAs are released as EV cargos is still questionable.…”
Section: Evs In Liver Diseasesmentioning
confidence: 99%
“…Recent studies also suggest the involvement of long noncoding RNAs (lncRNAs) in the pathogenesis of ALD. Yang et al 71 showed that lncRNAs, AK054921 and AK128652, are the two most abundantly expressed lncRNAs in normal human liver and that their levels were significantly elevated during ALD progression, indicating these two lncRNAs as novel candidates for ALD biomarkers. Whether these lncRNAs are released as EV cargos is still questionable.…”
Section: Evs In Liver Diseasesmentioning
confidence: 99%
“…5 The microRNAs (miRNAs) comprise a class of short single- stranded non-coding RNAs that regulate gene expression mainly through post-transcriptional regulation by binding to the 3â€ČUTRs of target mRNAs. For example, a new study demonstrated that miR-127 modulates the pluripotency of liver tumor initiating cells by targeting HMGB2.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…3 Extensive studies have been conducted on miRNAs, however the functions of lncRNAs remain poorly understood. 4,5 Recent studies have revealed that lncRNAs significantly impact on various biological processes as X-inactivation, genomic imprinting, chromatin modification, cell fate specification, cell apoptosis, nuclear trafficking, and genome rearrangement. 6 …”
Section: Introductionmentioning
confidence: 99%
“…They have also identified Heat shock protein 90 in ALD‐EVs as a mediator of macrophage activation. On the other hand, among transcriptomic approaches based on circulating small noncoding RNA (miRNA) and long‐noncoding RNAs (lncRNAs), several exosome‐associated miRNAs have been studied as potential biomarkers in preclinical studies . Briefly, in mouse models of ALD, serum levels of miR‐155 and miR‐122 were increased and, interestingly, enriched in circulating exosomes as well as miR‐192 and miR‐30a .…”
Section: Future Directionsmentioning
confidence: 99%